Colitis and Proctitis Caused by Pythium insidiosum in a Dog - Silva, Francisco Herbeson Aquino; Araújo, Bruno Vinícios Silva de; Sousa, Raylanne Letícia Pessoa; Gameleira, Jucélio da Silva; Fontes, Makson Diego de Paiva; Soares, Yanca Góes dos Santos; Galiza, Glauco José Nogueira de; Braga, Juliana Fortes Vilarinho (Acta Scientiae Veterinariae, 2025)
Background: Gastrointestinal pythiosis, caused by Pythium insidiosum, is a severe and underdiagnosed disease in dogs, posing significant diagnostic and treatment challenges. Brazil ranks 2nd globally in reported pythiosis cases, with 29 cases occurring in dogs, which exhibited the highest fatality rate among reported cases in the country, with most showing gastrointestinal involvement. Understanding this condition’s epidemiology and diagnostic intricacies is crucial for improving management strategies and outcomes in affected animals. We aimed to elucidate the clinical presentation, diagnostic findings, and outcomes of a gastrointestinal pythiosis case in a young dog from Mossoró, Brazil. Case: A 1-year-and-1-month-old, 20 kg male mixed-breed dog presented with gastrointestinal symptoms (vomiting, diarrhea, hematochezia, and weight loss) following the rainy season in Mossoró, Brazil. The dog, which had access to a balcony and brick-paved yard, had no direct rain exposure but fell ill shortly after the rainy period. Initial veterinary examination revealed eosinophilia (3,432 eosinophils/mm³), suggesting bacterial or parasitic gastroenteritis. Treatment included deworming, enrofloxacin, and multivitamins, leading to initial improvement. However, symptoms recurred, and 5 months later, the dog exhibited worsened symptoms, including significant weight loss (from 20 kg to 13 kg) and increased eosinophilia (4,224 eosinophils/mm³), prompting further evaluation. Abdominal ultrasonography indicated thickened colon walls (0.99 cm), loss of wall stratification, and a suspected neoplasm (4.25 cm × 2.90 cm). Exploratory laparotomy revealed extensive intestinal adhesions and hypervascularization, leading to euthanasia due to poor prognosis. Necropsy revealed whitish necrotic areas in the colon and rectum with enlarged lymph nodes showing necrotic foci. Histopathological examination confirmed transmural pyogranulomatous inflammation with fibrous tissue proliferation and infiltrating macrophages, plasma cells, eosinophils, and neutrophils. Multinucleated giant cells surrounded caseous necrotic areas containing intralesional fungal hyphae (4–10 μm in diameter, irregular branching). Grocott-Gomori’s methenamine silver (GMS) staining highlighted these hyphae, with strong immunostaining for P. insidiosum using immunohistochemistry. Discussion: This report describes a case of colitis, proctitis, and lymphadenitis in a young mixed-breed dog from Rio Grande do Norte’s semi-arid region, caused by P. insidiosum infection confirmed via immunohistochemistry. Post mortem diagnosis, following exploratory laparotomy, revealed advanced intestinal involvement that precluded surgical resection, highlighting the critical need for early diagnosis to improve prognosis. A previous case in the same region involved anal mucocutaneous junction lesions treated with itraconazole and terbinafine. In this present case, clinical signs including vomiting, diarrhea, hematochezia, and weight loss initially suggested parasitic gastroenteritis. Histopathological analysis confirmed pyogranulomatous inflammation with eosinophilic infiltrates and necrotic areas indicative of P. insidiosum hyphae, visualized with GMS staining. Immunohistochemistry confirmed P. insidiosum involvement, which was essential for a definitive diagnosis. This case highlights the diagnostic complexities and severe outcomes of gastrointestinal pythiosis in dogs, emphasizing the need for early detection and precise management to improve treatment outcomes in affected animals. Keywords: fungal-like infection, gastrointestinal infection, histopathology, immunohistochemistry, oomycetes, pythiosis.